Kurhany z epoki brązu nad górnym Dniestrem – polsko-ukraińskie projekty badawcze - Makarowicz, Przemysław; Lysenko, Siergiej D.; Kočkin, Igor T. (Folia Praehistorica Posnaniensia, 2013)
This paper discuses the excavations in the cemetery of the Komarów culture of the Bronze Age in Bukivna upon the upper Dniester. They have been carried out by the Polish-Ukrainian archaeological expedition as a part of the project of the National Centre of Sciences, the aim of which has been to provide comprehensive bioarchaeological characteristic and socio-cultural interpretation of the cemetery. During the field walking over 50 barrows were documented, round or slightly oval in plan. They occurred in three main clusters, arranged in groups-lines, on the watershed between the Dniester and its little, nameless tributary. The article presents the results of the study of barrow 1, in which there were discovered six features and over 400 artefacts, including 38 vessels in several deposits, 262 flint implements, fragments of structural daub, and bronze items - a pin and pendant, as well as small, burned bones. Among the features two charred wooden structures seem special and one stone-and-wood (cenotaph). Bones were “scattered” mainly between wooden structures. A series of analyses and specialist expertises had been done: radiocarbon, paleopedological, geomorphological, paleobotanical, physico-chemical. The sum of probability distribution of calibrated radiocarbon dates suggests second quarter of the second millennium BC. These dates are consistent with the analysis of the stylistics of vessels and bronze artefacts, indicating the early and classic stages of development of the Komarów culture.